Quality of life, resource utilisation and health economics assessment in advanced neuroendocrine tumours: a systematic review. (29th July 2013) - Chau, I.; Casciano, R.; Willet, J.; Wang, X.; Yao, J.C.
Abstract : Neuroendocrine tumours (NET) are often diagnosed at an advanced stage when the prognosis is poor for patients, who often experience diminished quality of life (QoL). As new treatments for NET become available, it is important to characterise the associated outcomes, costs and QoL. A comprehensive search was performed to systematically review available data in advanced NET regarding cost of illness/resource utilisation, economic studies/health technology assessment and QoL. Four rounds of sequential review narrowed the search results to 22 relevant studies. Most focused on surgical procedures and diagnostic tools and contained limited information on the costs and consequences of medical therapies. Multiple tools are used to assess health‐related QoL in NET, but few analyses have been conducted to assess the comparative impact of available treatment alternatives on QoL. Limitations include English language and the focus on advanced NET; ongoing terminology and classification changes prevented pooled statistical analyses. This systematic review suggests a lack of comparative economic and outcomes data associated with NET treatments. Further research on disease costs, resource utilisation and QoL for patients with advanced NET is warranted.